The Experience of Hypnobirthing in Wales: A Mixed Methods Study - SARAH LORD (2023)
Mixed methods were used to explore the experience of hypnobirthing in Wales. Hypnobirthing is a form of antenatal education and combines self-hypnosis with education regarding the physiology of birth. The self-hypnosis techniques are used to minimise fear and pain and create a sense of control in the birthing process. The classes portrayed a positive story of birth, which the participants found beneficial in a range of different forms of birth. Aim and Research Questions: The aim of this study focused on whether the learning and use of hypnobirthing improved thebirth experience of the participants. The research questions in Part Two comprised: Why do parents-to-be choose to complete a hypnobirthing course?; What is their experience of learning and using a hypnobirthing intervention?; Does the use of the intervention improve their experience of birth?; Are impact and outcome measures possible? and if so to outline; What helps and hinders the use of hypnobirthing? Methodology and Methods: The study setting was a University in Wales, at this site NHS and private hypnobirthing classes were provided by clinical and academic midwives, respectively. Part One constituted a retrospective pilot study, designed to collect initial qualitative data from those who had attended the private University classes. Part Two was designed as convergent mixed-method study. Observations were undertaken in the NHS and private classes. Participants from these classes were recruited for antenatal and postnatal interviews. A cross-sectional online survey was distributed across Wales. Findings: The findings are presented in four chapters, in Part One the importance of expectations and reality in the experience of hypnobirthing was introduced. In Part Two, the survey chapter presented a demographic picture and overview of the experience of hypnobirthing. The learning of hypnobirthing was detailed in The Stories of Hypnobirthing and considered the hypnobirthing mindset and impact of the COVID-19 pandemic. The use of hypnobirthing was explored with A Positive Birth and reviewed the physical and psychosocial impact of the intervention, as well as the factors that helped and hindered this experience. The hypnobirthing mindset was important to the participants in this study. Most participants felt that access to hypnobirthing should be wider. The contribution of hypnobirthing to a positive birth was established for the participants. Recommendations: A hypnobirthing intervention could be developed from this research and evaluated for effectiveness. Furthermore, the concept of a hypnobirthing mindset could be considered with a larger and more diverse population. In addition, the recommendations for clinical practice present the importance of the facilitation of hypnobirthing in all birth settings.